The Role of Resistine in the Fertility of Obese Infertile Males - Turki, Farah Mohommed Saleh (Iraqi Journal of Science, 2022)
Fertility is a major need for all humans and obesity has been shown an important factor that may affect it. Resistin is one of the adipokines that have a relation with both fertility and obesity. The study aimed to measure the resistin levels in serum and seminal fluid of normal fertile (n=10), obese infertile (n=20) and Non obese infertile (n=10) individuals using the enzyme linked immunoassay method (ELIZA), Also conventional semen analysis was performed for each sample. Results revealed a highly significant increase (p<0.01) in serum resistine levels in normal fertile males (7.4 ng/ml) compared to both non-obese and obese infertile males (1.13, 3.01 ng/ml) respectively the same results for seminal plasma resistin levels (12.1 ng/ml) compared to (2.1, 5.35 ng/ml) respectively. The results give an indication that resistine may have an influence on the fertility of obese males and this need further investigations in the molecular field of research.